Analysis of the sapta pesona and CBT concept in managing Alas Kedaton tourist attraction - Sumawidari, Ida Ayu Ketut; Mastiani Nadra, Nyoman; Wiwiek Ary Susyarini, Ni Putu (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This research aims to determine the extent to which 1) the Sapta Pesona concept and 2) CBT are applied in the management of the Alas Kedaton tourist attraction. Sapta Pesona Wisata is a value concept that was born and popularized by the former Minister of Tourism and Post and the New Order era, Soesilo Soedarman (1988-1993). Sapta Pesona Wisata which consists of security, cleanliness, order, coolness, beauty, hospitality, and providing memorable memories for tourists so that when tourists visit tourist attractions they get what they expected before visiting the tourist attractions. Meanwhile, the involvement of local communities in the management of a tourist attraction, known as CBT, is a basic element of tourism that places the community as an important factor in managing tourist attractions. Local communities have an important role in managing and developing these tourist attractions so that they remain sustainable. This research is qualitative research where data is obtained through interviews with management, library studies, observation, and documentation. All data obtained was collected then data reduction was carried out and a table was created and concluded. This research shows that the Sapta Pesona concept has been implemented and so has the CBT concept, but several aspects need to be strengthened so that the Alas Kedaton tourist attraction can provide maximum benefits for the local community.